The costs of SME’s financial distress: a cross-country analysis - Quintiliani, Andrea (Piccola Impresa / Small Business, 2017)
This paper stresses the importance of the intangibles, derivatives and local banks in determining SME’s financial distress costs. Many models exist in literature regarding the estimate of the probability of financial suffering but many of these neglect the importance of variables that are not properly accounting and that characterize business activity. Thus, an analysis was carried out to identify a number of qualitative elements that affect financial distress costs of small and medium-sized enterprises (SMEs). Findings allow to stimulating debate on policies to support SMEs.